Privacy-preserving decentralized detection in sensor networks - Sun, Meng (2019)
With a burgeoning number of Internet of Things (IoT) devices penetrating into all aspects of our lives, privacy-related issues are attracting increasing interest. Sensor network, one of the most important enabling technology of IoT, should be designed with privacy considerations. By giving users more control over what information can be shared from the sensors to the service providers, we will encourage the adoption of IoT technologies and put users at ease.